Properties and cost analysis of bio-urine liquid fertilizer (BLF) from Balinese cattle on the use of bio-activators and different fermentation times - Said, M. I.; Abustam, E.; Rohani, St.; Adiatma, R. N. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
The study was aimed to evaluate the effect of bio-activator and different fermentation time in the process of producing bio-urine liquid fertilizer (BLF) from Balinese cattle. Two types of bio-activators are used, namely (1) animal bio-activator (ABA) and (2) plant bio-activator (PBA). The time of fermentation process applied is (1) 7, (2) 14 and (3) 21 days. The research was prepared based on a Completely Randomized Design (CRD) of the factorial pattern. The data of the research were analyzed using ANOVA. The result showed that the difference of bio-activator and time of fermentation process had significant effect (P<0.05) on C-organic, N-organic and C/N ratio of BLF, but no significant on pH. The C-organic content of 9.59-12.02%. N-organic of 1.03-1.35% and C/N ratio of 8.33 to 11.03. The pH values are 8.76-8.95. The final results showed that the use of bio-activator using a 14-days fermentation time showed the best characteristics compared to other. The production cost of BLF using PBA is lower IDR.8,179.22 than ABA IDR.8.312,28. The application of PBA IDR.11,820.78, was more advantageous than ABA IDR.11,687.72.